Hip joint kinetics in the table tennis topspin forehand: relationship to racket velocity - Iino, Y. (Journal of Sports Sciences, 2018)
The purpose of this study was to determine hip joint kinetics during a table tennis topspin forehand, and to investigate the relationship between the relevant kinematic and kinetic variables and the racket horizontal and vertical velocities at ball impact. Eighteen male advanced table tennis players hit cross-court topspin forehands against backspin balls. The hip joint torque and force components around the pelvis coordinate system were determined using inverse dynamics. Furthermore, the work done on the pelvis by these components was also determined. The peak pelvis axial rotation velocity and the work done by the playing side hip pelvis axial rotation torque were positively related to the racket horizontal velocity at impact. The sum of the work done on the pelvis by the backward tilt torques and the upward joint forces was positively related to the racket vertical velocity at impact. The results suggest that the playing side hip pelvis axial rotation torque exertion is important for acquiring a high racket horizontal velocity at impact. The pelvis backward tilt torques and upward joint forces at both hip joints collectively contribute to the generation of the racket vertical velocity, and the mechanism for acquiring the vertical velocity may vary among players.